The nature of fluorescent antibody reactions in infections and artificial immunizations with Schistosoma mansoni - Sadun, Elvio H. (1962)
This paper describes studies in which Schistosoma mansoni eggs, miracidia, cercariae, schistosomula and adults were fixed with formol and stained with antibodies labelled with fluorescein isothiocyanate. The cuticle of the cercariae, cuticle of the schistosomula and ciliated epithelium of the miracidia were consistently and specifically reactive with labelled immune serum. In cercariae fixed with acetic acid and subsequently treated with immune serum followed by exposure to labelled antispecies globulin, the post-acetabular glands and ducts assumed a bright fluorescent stain. Absorption of sera that were reactive in the fluorescent antibody test and the cercarial slide flocculation test with antigen used in the latter removed the antibody reactive in both tests. The reproducibility of results with the indirect fluorescent antibody technique, employing different pools of cercariae and various lots of labelled antiglobulins, compared favourably with that in other serological procedures employing whole organisms. A correlation between the early appearance of fluorescent antibodies and the size of the cercarial inoculum was observed in Rhesus monkeys and albino mice. Fluorescent antibodies were detected much earlier in animals which are naturally resistant to S. mansoni infection. No fluorescent antibodies were detected in sera from infected St. Kitts and West African green monkeys, which are very susceptible to the disease. Schistosomula recovered from tissues gave identical results in the FA test to those obtained with the free-living cercariae and miracidia.